Developing Papuan cultural contextual E-Module learning devices in linear programs to improve students' mathematical problem-solving skills - Pakabu, Karunia Tumba Sanda; Sudirman, Sudirman; Kandaga , Thesa; Rodríguez-Nieto, Camilo Andrés; Dejarlo, Jenisus O. (International Journal of Mathematics and Sciences Education, 2024)
Using e-modules in learning has improved students' mathematical problem-solving abilities. However, the design of e-modules that integrate local culture is still rarely developed. This study aims to create a contextual e-module that reflects the culture of the Papuan community at State Vocational School I Agribusiness and Agrotechnology Nduga. This study used research and development (R&D) methods with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants in this study included material, language, media experts, teachers, and eleventh-grade students. Qualitative data were collected through respondent suggestions, and quantitative data were obtained through validation questionnaires and student testing. The analysis results showed that the Papuan cultural contextual e-module was valid, with percentages of 77.33% from material experts, 73.33% from language experts, and 68.88% from media experts. Teacher and student responses showed excellent practicality, with averages of 93.33% from teachers and 85.28% from students. In addition, the pre-test and post-test results showed a significant improvement in students' mathematical problem-solving abilities, with the KKM achievement level reaching 95.5% and a significance value (Sig. 2-tailed) < 0.001. Therefore, the contextual e-module based on Papuan culture can be an effective supplementary teaching material in mathematics learning, especially in linear programming material.